QRIS Cross-Border: Indonesia’s Soft Power Diplomacy Instrument in Payment Digitalization in Southeast Asia - Aryowiloto, Julang; Numadi, Katong Ragawi; Manggo, Thessalonicha Nathania (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2024)
The use of the Quick Response Code Indonesian Standard (QRIS) as a digital payment method has become widespread among the Indonesian population. This success can be attributed to the innovation and convenience offered by QRIS. Beyond Indonesia, QRIS can also be utilized as a digital payment method in countries such as Thailand, Malaysia, Singapore, Philippines, Vietnam, Laos, and Brunei Darussalam through the QRIS Cross-Border initiative. This paper aims to explore the trajectory of QRIS Cross-Border as a digital payment system applicable in most Southeast Asian countries, despite the existence of similar payment systems already in use within these nations. From the perspective of soft power diplomacy, this paper argues that Indonesia has effectively influenced the digital payment policy preferences of Southeast Asian countries by positioning QRIS Cross-Border as a tool of soft power. By leveraging the competitive advantages of QRIS Cross-Border, Indonesia has successfully attracted these nations to adopt it as their digital payment system. Nevertheless, the implementation of QRIS Cross-Border has not yet fully reached all countries in Southeast Asia.